Cell-surface proteomics for the identification of novel therapeutic targets in cancer. (4th March 2018) - Kuhlmann, Laura; Cummins, Emma; Samudio, Ismael; Kislinger, Thomas
ABSTRACT: Introduction : Cancer is the second most common cause of death worldwide and its heterogeneity complicates therapy. Standard cytotoxic regiments disrupt rapidly dividing cells, regardless of their neoplastic status. The introduction of less toxic targeted therapies has partially contributed to the observed decrease in cancer-related mortality. Cell-surface proteins represent attractive targets for therapy, due to their easily-accessible localization and their involvement in essential signaling pathways, often dysregulated in cancer. Despite their clinical appeal, cell-surface proteins are often underrepresented in standard proteomic data sets, due to their poor solubility and lower expression levels compared to intracellular proteins. Areas covered : This review will summarize some of the available techniques for enriching the cell-surface proteome, and discuss their advantages, limitations and applicability to clinical sample-testing. Moreover, we discuss currently available strategies for the development of novel targeted therapies in cancer. Expert commentary : The interest in elucidating the cancer-associated surfaceome is growing and will likely benefit from recent advancements in instrument sensitivity, method development, and a growing body of high-quality proteomics databases. Multiomics studies, in combination with functional validations (e.g. dropout screens), and evaluation of the healthy surfaceome, will likely aid in the selection of relevant targets for future therapy development.